ARTISTIC AND COMPOSITIONAL FEATURES OF CHILDREN’S COSTUME IN UKRAINE OF THE 20th – EARLY 21st CENTURIES - GERASYMENKO, O. D.; REMENIEVA, T. V.; FROLOV, I. V.; TRUSHYNA T. K., T. K. (Art and Design, 2022)
Purpose. The study of artistic imagery of children’s costume by Ukrainian fashion designers of the 20th – early 21st centuries, establishment of features and patterns in the repetition of artistic and compositional solutions of children’s costume, identification of established trends and innovations in the decoration of children’s clothing. Methodology. Visual-analytical method, morphological, artistic-compositional and retrospective analysis were applied. Results. As a result of the analysis of children’s clothing models of Ukrainian designers and brands, the artistic and compositional features of children’s costumes and current trends in the decoration of children’s clothing of the 20th – early 21st centuries are identified. It is determined that during this period, possibilities for the implementation of artistic imagery of clothing for children have expanded due to innovative materials and decoration technologies, but even in our time, traditional types of decoration that have been characteristic of children’s costumes for centuries do not lose their relevance. The scientific novelty of the research consists in identifying features of artistic and figurative solutions of children’s clothing by designers of Ukrainian fashion houses and leading trends in the decoration of children’s costumes in Ukraine of the 20th – early 21st centuries. Practical significance. The collected materials and their analysis allowed to summarize information about artistic solutions and children’s costumes by designers of Ukrainian fashion houses, which can serve as a basis for further research on the history of fashion and children’s clothing design, information base for creating new collections of children’s clothing.